Application of the Six Sigma Method to Improve the Quality of Cocoa Oil Industry Products in Southeast Sulawesi Province, Indonesia - Sudirman Zaid; Nasrul Nasrul (Journal of Global Innovations in Agricultural Sciences)
This research aims to control the quality of cocoa oil industry products through the application of the six sigma method. This research was carried out in the cocoa oil industry centre area in Southeast Sulawesi Province, which accommodates 3 (three) regions, namely; North Kolaka Regency, East Kolaka Regency, and Kolaka Regency. The population in this study were owners or managers of the cocoa oil industry, totalling 130 industries. The research sample used census techniques, namely; the entire population is used as a sample. Data collection techniques were carried out through interviews and direct observation at each industrial location during the cocoa oil production process. The analysis used in this research is Six Sigma analysis with the Define, Measure, Analysis, Improve, and Control (DMAIC) approach. The research results show that there is an average of 17.74% defective cocoa oil products for each production. In addition, the results of this study show that the types of defective cocoa oil products are smell mismatch (17.74%), color (3.71%), taste (7.60%), and water content (70.95%). The results of this research also provide information that the solution needed to control the quality of cocoa oil products is replacing production equipment and production support, establishing partnerships with cocoa bean suppliers from more profitable sources, improving the soft and hard skills of the workforce as well as mentoring, providing machines. more adequate packaging, as well as the use of ethanol solution in the extraction process.